2017
DOI: 10.1016/j.ctro.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Significant tumor shift in patients treated with stereotactic radiosurgery for brain metastasis

Abstract: IntroductionLinac-based stereotactic radiosurgery (SRS) for brain metastases may be influenced by the time interval between treatment preparation and delivery, related to risk of anatomical changes. We studied tumor position shifts and its relations to peritumoral volume edema changes over time, as seen on MRI.MethodsTwenty-six patients who underwent SRS for brain metastases in our institution were included. We evaluated the occurrence of a tumor shift between the diagnostic MRI and radiotherapy planning MRI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The timing of steroid administration was the predictive factor of tumor reduction, displacement and shape change. The correlation between the shift of center of PTV and change in edema volume was mentioned in previous report [13]. As steroid administration reduced the surrounding edema [14], displacement and shape change might have been caused.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The timing of steroid administration was the predictive factor of tumor reduction, displacement and shape change. The correlation between the shift of center of PTV and change in edema volume was mentioned in previous report [13]. As steroid administration reduced the surrounding edema [14], displacement and shape change might have been caused.…”
Section: Discussionmentioning
confidence: 76%
“…This study reported MRI appearance changes during linac-based SRT for large brain metastases, and analyzed the lesions necessitating treatment plan modification. Some studies reported about tumor changes in a short period between planning MRI and STI start, such as tumor size and shift [12, 13]. However, there were few studies mentioned about the detail changes of tumor during SRT periods [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Specific entities are metastases, primary brain tumors (low-grade gliomas, anaplastic astrocytomas, oligodendrogliomas, glioblastomas), extra-axial tumors such as meningioma, and other benign entities including pituitary adenomas and vestibular schwannomas. A MRI-based planning workflow could potentially be both, cost- and time-saving while reducing uncertainties associated with CT-MRI registration [4]. MRI already represents the gold-standard imaging method for brain tumor diagnosis and the assessment of treatment response [5].…”
Section: Clinical Sitesmentioning
confidence: 99%
“…However, a crucial difference emerges: the MRL systems enable a rapid adaptation, immediate target volume delineation [6] and quick tumor response assessment. An example is the treatment of a resection cavity, which can change significantly in shape and size between the simulation MRI and the initiation of treatment [4]. Furthermore, if hypofractionated stereotactic radiosurgery (SRS) is applied, the resection cavity could also change during the treatment course of 3–5 fractions, which would be visible using MRgRT.…”
Section: Clinical Sitesmentioning
confidence: 99%
“…The CT scan provides electron density information necessary for dose calculations in the currently commercially available treatment planning systems. The MRI is used for anatomical information (especially tumour extent) and is usually acquired shortly before RT delivery as progression and shifting of the lesions over time has been shown to occur in patients with brain metastasis [1] . A contrast-enhanced T1-weighted sequence is the recommended MRI simulation reference image for intracranial stereotactic radiotherapy (SRT) [2] .…”
Section: Introductionmentioning
confidence: 99%